Board Gender Diversity, Auditor Fees, and Auditor Choice - Lai, Karen M. Y.; Srinidhi, Bin; Gul, Ferdinand A.; Tsui, Judy S. L. (Contemporary Accounting Research, 2017)
Abstract We examine whether the presence of female directors and female audit committee members affect audit quality in terms of audit effort and auditor choice by using observations from a sample of U.S. firms, spanning the years 2001–2011. We find, after controlling for endogeneity and other board, firm, and industry characteristics, that firms with gender‐diverse boards (audit committees) pay 6 percent (8 percent) higher audit fees and are 6 percent (7 percent) more likely to choose specialist auditors compared to all‐male boards (audit committees). Our findings suggest that boards (audit committees) with female directors (members) are likely to demand higher audit quality, ceteris paribus.